Strength properties of self-compacting concrete incorporating iron ore tailings (2023)
The quest for sustainable production of concrete is a major step towards achieving netzero Carbon. The utilisation of industrial waste in the production of concrete entrenches both sustainability and economic viability. Iron Ore Tailings (IOT) are a byproduct of the beneficiation process of iron ore. The unbridled disposal of Iron Ore Tailings (IOT) has proven to be a great threat to the natural environment. Self-compacting concrete (SCC) has gained prominence in the construction industry based on its unique flowability quality. This study investigated the strength characteristics of SCC incorporating IOT as replacement for fine aggregate. Concrete containing 5%, 10%, 15%, 20%, 30%, 40%, and 100% IOT as fine aggregate replacement were prepared and subjected to compressive and flexural strengths tests. The results reveal a progressive increase in strength with age for compressive strength, and progressive increase in strength with increasing percentage contents of IOT for both compressive and flexural strength tests. The inclusion of IOT as partial replacement of fine aggregates in SCC has a potential to mitigate the environmental degradation caused by its disposal and excessive depletion of natural sand. Besides, it is a viable measure towards reduction of carbon footprint of concrete production with evident economical benefits.